High-throughput sugarcane leaf analysis using a low cost closed-vessel conductively heated digestion system and inductively coupled plasma optical emission spectroscopy - Miranda, Kelber [UNESP]; Vieira, Alan Lima [UNESP]; Gomes Neto, José Anchieta [UNESP] (Royal Soc Chemistry, 2014)
Most small to medium-size laboratories involved in foliar diagnosis make use of digestion blocks with borosilicate glass tubes to decompose leaf samples. Then, the elements of interest can be simultaneously determined by ICP OES, except boron, because blank signals for this element are greater than the analytical signals. To determine boron by ICP OES, all samples are digested again using a dry ashing procedure, sometimes requiring up to 24 h per a small group of samples. In order to provide a low-cost alternative to prepare leaf samples for elemental determination, including boron, quartz digestion tubes were developed for the recently proposed closed-vessel conductively heated digestion system (CHDS). The performance of the CHDS with quartz tubes was evaluated by converting sugarcane leaf samples into solutions for subsequent determinations of macro- (Ca, K, Mg, P, and S) and micronutrients (Al, B, Cu, Fe, Mn and Zn) by ICP OES. The analytical procedure was validated with three certified reference materials and applied to ten sugarcane leaf samples. The results obtained for Al, B, Ca, Cu, Fe, K, Mg, Mn, P, S and Zn determined by ICP OES and the conductively heated digestion system with quartz tubes were in fair agreement with those obtained after closed-vessel microwave-assisted digestion. For all elements determined, the relative standard deviation (n = 3) was usually below 5%. The use of quartz digestion tubes resulted in lower blank values for boron, allowing the determination of all elements of interest in one run.